Trilhas ecológicas como recurso didático para a educação ambiental: integrando Geografia e Educação Física - Bessa, Chera Rosane Leles de (Instituto Federal de Educação, Ciência e Tecnologia do Tocantins, 2022)
This work has its essence in the constructs of an integrative way of educating that aims to discuss the relevance of thinking pedagogical strategies for an interdisciplinary curriculum, as well as to motivate the innovation of teaching-learning practices in the professional and technological high school education. The goal was to build a didactic model that considered the intersections between environmental education, geography, and physical education, with the use of virtual ecological trails and various technological resources to contribute to the integral/omnilateral human formation of students at the Federal Institute of Education, Science, and Technology of Tocantins, Palmas Campus. This is qualitative research, with a triangulation between bibliographic research, documentary research, and action research. After the investigations, interventions and data analysis, the study revealed that interdisciplinarity is a challenge and a possibility to contribute to the integral formation of the subjects, and that the use of natural spaces, such as ecological trails, and different technological resources are positive for the expansion of criticality, the development of the students and the updating of the professional and technological education at a high school level. As a result, this work also presented a didactic script entitled Trilhando a interdisciplinaridade na EPT – diálogos entre geografia, educação física e educação ambiental (Tracking interdisciplinarity in EPT – dialogues between geography, physical education, and environmental education), as a satisfactory material for the approximation of different knowledge for the expansion of dialogues on critical and powerful environmental education for a more human and integral formation.